Formação e práticas docentes de educação física em contextos terapêuticos - Barros, Naranúbia Lima (2021)
This research is willing to understand the relations between the initial training of Physical Education teachers and the dynamics of their actions that are located on the borde between education and health, a discussion that will start from the assumptions that underlie the research line Formação de Professores e Práticas Docentes, which intrinsically leads us to the problematization of training always together with the characterization and analysis of praxis. Thus, the problem that guides this research is: to what extent the Physical Education teacher's training enables this professional to act in border contexts between health and education? The goal is to understand to what extent the physical education teacher feels prepared to work with equine therapy, considering the learning acquired during the initial training of Physical Education graduates and their methods for teaching practices in contexts different from the school. In order to better analyze training and practice, we will investigate them from three perspectives: that of the training institution (IFRR); that of the trained teacher, working in equine therapy; and that of the resolutions, laws and other documents that regulate the training and performance of the Physical Education teacher, thus configuring a research with data triangulation. Our analyses come from the information we gathered from the questionnaire with the teachers, from the interview with the coordinator of the Physical Education undergraduate course at IFRR, and from the document analysis. This research took paths that legitimized the importance of experience and reflection as processes of formation. We discussed if equine therapy is more of an educational or health action, and we understood, from then on, that the health field is somewhat more explored by these professionals, in a very well grounded way, given the origin of Physical Education. As for the training institution, we understand that it is based on the idea of training professionals for the school, although it occasionally explores other spaces.